Pengembangan Dashboard Eksekutif untuk Sistem Monitoring Penanganan Filariasis Kota Pekalongan - Maulana, Mohammad Reza; Susanto, Eko Budi; Christianto, Paminto Agung (JURNAL LITBANG KOTA PEKALONGAN, 2021)
Pekalongan City still has a Microfilaria Rate rate of more than one percent based on a survey from 2011 to 2015. This causes the Pekalongan City Health Office to repeat POPM activities for the next two years. It is hoped that this incident will not be repeated in the following years. One of the obstacles faced is the absence of monitoring in the administration of elephantiasis medicine. In general, elephantiasis medication has been given well, but the community’s level of adherence to taking filiaris medication is still low. So that the efforts that have been made by the Health Office have not been able to break the chain of filariasis disease. One solution to this problem is to apply the RT/RW executive dashboard application which in previous research has been developed in the form of a prototype. In this study, a prototype of the RT/RW executive dashboard will be developed so that it can be used to carry out monitoring activities for filariasis drug administration. Keywords: Executive dashboard, filariasis, prototype